2003
DOI: 10.1207/s15374424jccp3202_13
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Relationship in Child Therapy: Perspectives of Children and Mothers

Abstract: Examined qualities of the therapeutic relationship as perceived by low-income children who were in treatment for serious emotional disorders and their mothers. Recent emphasis on engaging families in the treatment of their children highlights the importance of understanding processes that facilitate therapeutic partnerships. Therapeutic bonds (i.e., the closeness of the relationship to therapist) for both children and their mothers were assessed. One-hundred fifty-seven families participated. Cross-sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Twelve items are rated on a Likert scale from 1 (not true) to 4 (very much true). The TASC-r scores have demonstrated good reliability and validity in previous studies (Creed & Kendall, 2005; DeVet, Kim, Charlot-Swilley, & Ireys, 2003). …”
Section: Methodsmentioning
confidence: 71%
“…Twelve items are rated on a Likert scale from 1 (not true) to 4 (very much true). The TASC-r scores have demonstrated good reliability and validity in previous studies (Creed & Kendall, 2005; DeVet, Kim, Charlot-Swilley, & Ireys, 2003). …”
Section: Methodsmentioning
confidence: 71%
“…The Therapeutic Alliance Scale for Children is unique among alliance measures in that it was designed specifically for use with children and adolescents. It assesses positive and negative aspects of the therapeutic alliance (e.g., "I liked spending time with my therapist" ; "When I was with my therapist, I wanted the session to end quickly") and has demonstrated reliability and validity in previous investigations (DeVet, Kim, Charlot-Swilley, & Ireys, 2003;Shirk & Saiz, 1992). In this study, youth alliance demonstrated excellent internal consistency (α = .93), and adequate 7-to 14-day test-retest reliability of r =.…”
Section: Methodsmentioning
confidence: 73%
“…The TASA is an upward extension of the Therapeutic Alliance Scale for Children (Shirk & Saiz, 1992). In multiple studies, the TASC has been shown to have excellent internal consistency, good test-retest reliability (Creed & Kendall, 2005;DeVet, Kim, Charlot-Swilley, & Ireys, 2003;Shirk & Saiz, 1992), and moderate to large associations with other measures of relationship quality (Cavell & Hughes, 2000), including observed alliance (McLeod & Weisz, 2005). For the TASA, stems were modified to be appropriate for adolescents and items were rated on a 6-point rather than a 4-point scale from not true at all to very true.…”
Section: Methodsmentioning
confidence: 99%